Respuesta :
Answer:
(7, -2)
Step-by-step explanation:
x + 3y = 1
-3x - 3y = -15
(x-3x) + (3y-3y) = 1-15
-2x + 0 = - 14
-2x = - 14
x = 7
x + 3y = 1
7 + 3y = 1
3y = 1-7
3y = -6
y = -2
Answer:
D: (7 , -2)
Step-by-step explanation:
Multiply each equation by the value that makes the coefficients of x
opposite.
(3)⋅(x+3y)=(3)(1)
−3x−3y=−15
Simplify
3x+9y=3
−3x−3y=−15
Add the two equations together to eliminate x
from the system.
3x+9y= 3
+ −3x−3y=−15
_____________
6y=−12
Divide each term by 6 and simplify.
y=−2
Substitute the value found for y into one of the original equations, then solve for x.
x=7
The solution to the independent system of equations can be represented as a point.
(7,−2)
The result can be shown in multiple forms.
Point Form:
(7,−2)
Equation Form:
x=7, y=−2
I hope this helps!!!!!!!